2001
DOI: 10.1074/jbc.m010534200
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of Human Mucin GeneMUC5B in Gastric Carcinoma and Cancer Cells

Abstract: In gastric cancer, altered expression of MUC1, MUC2, MUC5AC, and MUC6 mucin genes has already been described. We show in this report by the means of in situ hybridization, reverse transcriptase-polymerase chain reaction, and transfection assays that MUC5B is also abnormally expressed in gastric carcinomatous tissues and cell lines. We thus undertook to elucidate the molecular mechanisms that regulate the transcription of MUC5B in gastric cancer cells. To this end, high expressing (KATO-III) and low expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 51 publications
5
59
1
Order By: Relevance
“…Several studies have examined the expression of various mucin genes in relation to the nature and extent of CpG island methylation, and have found that MUC2 and MUC5B in particular, show strong correlations between promoter methylation and suppression of mucin protein synthesis. 23,[54][55][56][57] There is currently little or no evidence of methylation-induced silencing of either MUC5AC or MUC6. 23 Furthermore, MUC17, a transmembrane mucin gene, is regulated by promoter CpG island methylation and histone H3-K9 acetylation in pancreatic ductal adenocarcinomas, where promoter hypomethylation is associated with MUC17 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the expression of various mucin genes in relation to the nature and extent of CpG island methylation, and have found that MUC2 and MUC5B in particular, show strong correlations between promoter methylation and suppression of mucin protein synthesis. 23,[54][55][56][57] There is currently little or no evidence of methylation-induced silencing of either MUC5AC or MUC6. 23 Furthermore, MUC17, a transmembrane mucin gene, is regulated by promoter CpG island methylation and histone H3-K9 acetylation in pancreatic ductal adenocarcinomas, where promoter hypomethylation is associated with MUC17 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Fragments were gel-purified as in Perrais et al (2001a) before being methylated with mSssI for 3 h at 371C (New England Biolabs, OZYME, France). The degree of methylation of the fragment was confirmed by testing its resistance to HpaII digestion.…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
“…The methylated fragments were then ligated into pGL3 basic vector. DNA concentration was measured at 260 nm before being used in transfection experiments as described in Perrais et al (2001a). Influence of methylation on Sp1 transactivation of the promoters was studied by carrying out cotransfections in triplicate in three separate experiments in the presence of pCMV-Sp1 expression vector as described in Van Seuningen et al (2000).…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Certain cancer cell types methylate the BubR1, 7-dehydrocholesterol reductase (Dhcr7), aquaporin-5 (AQP5), RUNX3, lysophosphatidic acid receptor-1 (lpa1), galectin-3, CDX1, MUC5B, PDZ-LIM domain-containing protein 2 (PDLIM2), LOT1 (PLAGL1/ZAC1), TNFSF7 (CD70) genes, leading to their transcriptional suppression DNA hypomethylation at CpG islands within the promoters (Abdollahi et al, 2003;Ahmed et al, 2007;Kim et al, 2005;Motegi et al, 2005;Park et al, 2005;Perrais et al, 2001;Qu et al, 2010;Suh et al, 2002;Tsujiuchi et al, 2006;Yu et al, 2010). The upregulation of galectin-7, CDX4, and urokinase-type plasminogen activator (uPA), and MMP-2 genes in several cancer types including breast cancer, ovarian cancer, and lymphoma cells is mediated by DNA hypomethylation (Chernov et al, 2009;Demers et al, 2009;Guo et al, 2002;Honda et al, 2006;Pakneshan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%